SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PEMBELIAN UNTUK MENYUSUN LAPORAN LABA RUGI DAN MENGUKUR RASIO PROFITABILITAS (STUDI KASUS TOKO EKA JAYA ELEKTRONIK) - Oktovia Rukfani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
The development of technology is now something that is universal and can be utilized in various human lives. One of them is in business. In this era, it is undeniable that a computer is a component that must be owned by a company in running its business, in order to assist in processing data and help improve the quality of work and quality of service. In this case, Eka Jaya Electronics Shop is used as a place of research, because in this place the system is still manual and not well managed, so that errors often occur in making reports and in processing stock. The purpose of this study is to provide convenience when processing sales, purchasing, product data, supplier data and customer data, minimizing errors in recording. The research method used in this study is to use the R & D (Research and Development) method. This method is used to produce a certain product that is analytical and its effectiveness can be tested so it can be used in the wider community. In designing the system tools used are Flowcharts, Entity Relationship Diagrams and Context Diagrams, while for data collection using observation, interviews, and literature study. Database application development tools using MySQL and programming languages ​​using Visual Basic 6.0. With this information system, transaction data processing can be computerized so as to reduce errors in reporting. Keywords: Accounting Information Systems, Sales and Purchases, R&D Methods